The important of designing legislation on Indonesian contempt of court act: legal practitioners perspective - Siti Zulaichah (Universitas Muhammadiyah Magelang, 2023)
Contempt of court term in Indonesia has been initially originated in the general definition of Law 14th 1985 on Supreme Court item 4 paragraph 4. In that general definition, it implied an obligation to confirm the law soon specifically regulating about the contempt of court in Indonesia. The perspective of legal experts and practitioner, were expected to contribute within the implementation of contempt of court regulation. Controversy on contempt of court started being a polemic as Law Draft of Criminal Code has appeared, in which within one of this law draft has inserted articles about contempt of court. This research was aimed to analyze factors that could cause contempt of court and its urgency in forming the regulation of contempt of court in Indonesia. The method in this research was juridical-empirical method. Moreover, the researchers in this research attempted to describe point of views of legal practitioners in Malang that were obtained from interview and observation with judges, prosecutors, and lawyers. The researchers used qualitative approach as the type of research approach. This research result explained that the prevalence of contempt of court case until recently was appeared due to the lack of public awareness in complying with the law and low ethical behavior of the law of either the society or law enforcer.